Investigation on the Space Patterns and Influential Factors for Distribution of Traditional Villages in Sichuan - Hua, Z. Z.; Jamaludin, Omar; Doh, Shu Ing (Penerbit UMP, 2024)
Traditional villages encapsulate the core of traditional culture and represent an indispensable element for rural revitalization. Nevertheless, over the past few decades, the continuous expansion of urban areas has resulted in the destruction of these villages. It holds immense importance to scrutinize the spatial arrangement and factors influencing the safeguarding and advancement of traditional villages. Previous research has predominantly concentrated on the value and protective mechanisms of traditional villages, overlooking their spatial distribution attributes and influencing factors. Hence, The paper focus on 396 traditional villages in Sichuan. Google Earth was utilized to rectify the longitude and latitude coordinates of villages. ArcGIS 10.8 and Geo-detector 2015 software was employed to examine the geographical distribution and influencing factors of traditional villages in Sichuan. The findings revealed that: (1) Sichuan traditional villages exhibit a clustered distribution, with the highest concentration found in Bazhong and Guangyuan cities in northeast Sichuan. Following closely are Li County of Aba Prefecture, Danba County of Ganzi Prefecture in northwest Sichuan, the junctions of Zigong, Neijiang, and Luzhou in southern Sichuan, and the junctions of Ya'an, Meishan, and Leshan in the Chengdu Plain. (2) Traditional villages in Sichuan are impacted by natural environmental and socio-economic factors, with temperature, altitude, precipitation, and distance from cities significantly affecting their distribution. (3) Approaches for the conservation and advancement of those villages include supporting spontaneously organized eco-friendly and sustainable agricultural projects by farmers, as well as planning the development of concentrated and contiguous tourism industries while protecting the ecological environment.